Lethal osteogenesis imperfecta congenita and a 300 base pair gene deletion for an alpha 1(I)-like collagen. Issue 6415 (11th February 1984) - Pope, F M; Cheah, K S; Nicholls, A C; Price, A B; Grosveld, F G
Abstract : Broad boned lethal osteogenesis imperfecta is a severely crippling disease of unknown cause. By means of recombinant DNA technology a 300 base pair deletion in an alpha 1(I)-like collagen gene was detected in six patients and four complete parent-child groups including patients with this disease. One from each set of the patients' clinically unaffected parents also carried the deletion, implying that affected patients were genetic compounds. The study suggests that prenatal diagnosis should be possible with 100% accuracy in subjects without the deletion and with 50% accuracy in those who possess it (who would be either heterozygous--normal, or affected with the disease).